Autologous CIK Cell Immunotherapy in Patients with Renal Cell Carcinoma after Radical Nephrectomy - Yajing Zhang; Jin Wang; Yao Wang; Xue-Chun Lu; Hui Fan; Yang Liu; Yan Zhang; Kai-Chao Feng; Wen-Ying Zhang; Mei-Xia Chen; Xiaobing Fu; Wei-Dong Han (Clinical and Developmental Immunology)
Objective. To evaluate the efficacy of autologous cytokine-induced killer (CIK) cells in patients with renal cell carcinoma (RCC). Methods. 20 patients diagnosed with TNM stage I or II RCC were randomly divided into two groups, a CIK cell treatment group and a control group. The endpoint was progression-free survival (PFS) evaluated by Kaplan-Meier analyses. Results. CD3+, CD3+/CD8+, CD3+/CD4+, and CD3+/CD56+ levels increased after CIK cell culture (P<0.01). The median PFS in CIK cell treatment group was significantly longer than that in control group (PFS, 32.2 months versus 21.6 months; log-rank, P=0.032), all patients were alive during the course of followup, and there are no statistically significant differences between two groups in OS (log-rank, P=0.214). Grade III or greater adverse events were not observed. Conclusions. CIK cells treatment could prolong survival in patients with RCC after radical nephrectomy and showed acceptable curative effect with potential enhancement of cellular immune function. This trial is registered with Clinicaltrials.gov NCT01799083.